Replication of Hepatitis C Virus Subgenomes in Nonhepatic Epithelial and Mouse Hepatoma Cells - Zhu, Qing (American Society for Microbiology, 2003)
The hepatitis C virus (HCV) pandemic affects the health of more than 170 million people and is the major indication for orthotopic liver transplantations. Although the human liver is the primary site for HCV replication, it is not known whether extrahepatic tissues are also infected by the virus and whether nonprimate cells are permissive for RNA replication. Because HCV exists as a quasispecies, it is conceivable that a viral population may include variants that can replicate in different cell types and in other species. We have tested this hypothesis and found that subgenomic HCV RNAs can replicate in mouse hepatoma and nonhepatic human epithelial cells. Replicons isolated from these cell lines carry new mutations that could be involved in the control of tropism of the virus. Our results demonstrated that translation and RNA-directed RNA replication of HCV do not depend on hepatocyte or primate-specific factors. Moreover, our results could open the path for the development of animal models for HCV infection.